Translation Techniques Used in Indonesian-English Translation of Culture-Bound Words in “Cantik Itu Luka” and The Resulting Quality - Ulya Dewi, Fitri; Yuliasri, Issy; Rustipa, Katharina (Institut Agama Islam Negeri Palopo, 2025)
This study analyzes the translation of culture-bound words in the novel Cantik Itu Luka by Eka Kurniawan and its English version, Beauty is A Wound, translated by Annie Tucker. The study aims to identify the techniques used in culture-bound words and the resulting quality. The culture-bound words category was analyzed using Newmark, (1988). Meanwhile, the theory of translation techniques proposed by Molina & Albir, (2002) used to identify translation techniques applied by translators in translating culture-bound words. Text studies, reading, taking notes, and in-depth analysis using table instruments are all part of this qualitative research approach. Further, the author used accuracy, acceptability, and readability rating instruments based on Larson, (1998) to determine the translation quality of culture-bound words. The finding showed 434 culture-bound words found in this novel, and 14 translation techniques were identified, with the established equivalent being most frequent at 36.81%. Moreover, the average accuracy was 88.99%, clarity was 82.24%, and naturalness was 79.80%. This research attempts to improve knowledge of the translation process and its function in cross-cultural communication by comprehending the translation techniques and quality that underlie the translation of culture-bound words.